HER2 expression in different cell lines at different inoculation sites assessed by [52Mn]Mn-DOTAGA(anhydride)-trastuzumab - Toàn Minh Ngô; Toàn Minh Ngô; Adrienn Vágner; Gábor Nagy; Gábor Ország; Tamás Nagy; Tamás Nagy; Zoltán Szoboszlai; Csaba Csikos; Csaba Csikos; Balázs Váradi; György Trencsényi; et al. (Pathology and Oncology Research)
PurposePositron emission tomography (PET) hybrid imaging targeting HER2 requires antibodies labelled with longer half-life isotopes. With a suitable radiation profile, 52Mn coupled with DOTAGA as a bifunctional chelator is a potential candidate. In this study, we investigated the tumor HER2 specificity and the temporal biodistribution of the [52Mn]Mn-DOTAGA(anhydride)-trastuzumab in preclinical models.MethodsPET/MRI and PET/CT were performed on SCID mice bearing orthotopic and ectopic HER2-positive and ectopic HER2-negative tumors at 4, 24, 48, 72, and 120 h post-injection with [52Mn]Mn-DOTAGA(anhydride)-trastuzumab. Melanoma xenografts were included for comparison of specificity.ResultsIn vivo biodistribution demonstrated strong contrast in HER2-positive tumors, particularly in orthotopic tumors, where uptake was significantly higher than in the blood pool and other organs from 24 h onwards and consistently higher than in ectopic HER2-positive tumors at all time points. Significantly higher tumor-to-blood and tumor-to-muscle ratios were observed in HER2-positive ectopic tumors compared to HER2-negative tumors but only at 4 and 24 h; the differences were likely due to non-specific binding of the tracer. The ratios for orthotopic HER2-positive tumors were significantly higher than those for ectopic HER2-negative tumors and melanoma at all time points. However, the differences between HER2-positive and HER2-negative tumors decreased at later time points.ConclusionThese results suggest that [52Mn]Mn-DOTAGA(anhydride)-trastuzumab demonstrates efficient tumor-to-background contrast, emphasize the higher tumor uptake observed in orthotopic tumors, and highlight the influence of tumor environment characteristics on uptake.